2002
DOI: 10.1100/tsw.2002.111
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Land-Use Impact on Macroinvertebrate Communities in the Zwalm River Basin (Flanders, Belgium) Using Multivariate Analysis and Geographic Information Systems

Abstract: Relationships between land-use and river water quality assessed by means of biological and physical-chemical variables and habitat characteristics were analysed for the Zwalm River basin in Flanders (Belgium). The research focussed on three zones within this river basin, each characterized by different land uses, and consequently, different types of pollution, mainly of diffuse origin. Environmental data have been integrated within a Geographic Information System. Possible relationships between aquatic ecosyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This idea is also supported by the fact that the predictive power of water quality parameters for macroinvertebrate communities increases with the number of parameters measured [37]. Physical-chemical variables are often less important than hydromorphological variables, such as the water regime or sediments, which are variables controlled by other processes at the watershed and valley segment scales [49][50][51]. In rivers affected by discharges with high organic loads or toxic effluents or with a high area of intensive agriculture in their drainage basins, the opposite occurs, and water quality is the main factor in the structure of the macroinvertebrate community [43,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea is also supported by the fact that the predictive power of water quality parameters for macroinvertebrate communities increases with the number of parameters measured [37]. Physical-chemical variables are often less important than hydromorphological variables, such as the water regime or sediments, which are variables controlled by other processes at the watershed and valley segment scales [49][50][51]. In rivers affected by discharges with high organic loads or toxic effluents or with a high area of intensive agriculture in their drainage basins, the opposite occurs, and water quality is the main factor in the structure of the macroinvertebrate community [43,49].…”
Section: Discussionmentioning
confidence: 99%
“…Physical-chemical variables are often less important than hydromorphological variables, such as the water regime or sediments, which are variables controlled by other processes at the watershed and valley segment scales [49][50][51]. In rivers affected by discharges with high organic loads or toxic effluents or with a high area of intensive agriculture in their drainage basins, the opposite occurs, and water quality is the main factor in the structure of the macroinvertebrate community [43,49]. In the Turón River, the diffuse agricultural and direct urban discharges that occur in the dry season (summer and autumn) exert, as in other Mediterranean rivers [35,52,53], a greater weight on the water quality at the local scale.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the two rivers had different loads of micro-pollutants and Nitrogen, resulting in different bryophyte recolonisation patterns. At the Zwalm River basin in Flanders, Adriaenssens et al (2002) analysed the relationships between land use and river water quality using biological, physical-chemical, and environmental factors. In Flanders, signi cant problems with water quality were caused by pollution from nonpoint sources, mostly from agricultural and household sources.…”
Section: Aquatic Environment Pollution and Implications For Aquatic H...mentioning
confidence: 99%
“…In Flanders, signi cant problems with water quality were caused by pollution from nonpoint sources, mostly from agricultural and household sources. Adriaenssens et al (2002) further revealed that land-use activities had a more signi cant in uence on macroinvertebrate communities than changes in the environment's physical-chemical features. Therefore, this should be considered when designing ecological indicators.…”
Section: Aquatic Environment Pollution and Implications For Aquatic H...mentioning
confidence: 99%
“…Macroinvertebrates are organisms that are touted as important biological indicators for monitoring freshwater ecosystem worldwide because of their high sensitivity to changes in water quality, food and habitats. They are also easy to capture for sampling due to their limited mobility which can be retained by a mesh net size 200 -500 micro meter (Adriaenssens et al, 2002;Hussain and Pandit, 2012;Sharifinia, 2015). However, inevitable changes in our environment like increased number of population, uncontrolled agricultural practices, and industrial development are major reasons in altering ecological balance on our aquatic ecosystem.…”
Section: Introductionmentioning
confidence: 99%